A STUDY OF ENTERPRISE VALUE IN INDONESIAN MANUFACTURING FIRMS: EVIDENCE FROM IDX-LISTED COMPANIES - Winda Dwi Yanthi; Eddo nanda Oktarici (Pusat P2M Politeknik Negeri Batam, 2025)
The research study examined the influence debt policy, profitability, company performance, and investment decisions on the value of enterprises within the manufacturing sectors which listed on the Indonesia Stock Exchange (IDX) from 2018 into 2022. We included 15 companies in the sample and conducted the analysis using multiple linear regression with SPSS 25. The findings indicated that the debt policy (DER) had a significant negative impact on firm value, evidenced by a t count of -3.178 and a significance level of 0.002. The impact of profitability (ROE) on firm value is notably positive, as evidenced by a t amount of 9.110 and a significance level 0.000. The company performance, measured by ROA, had a significantly negative impact on enterprise value, evidenced by a t count of -0.3288 and a significance level 0.002. In the meantime, investment decisions (CAPBVA) do not significantly influence enterprise value, as indicated by a t count of 1.991 and a corresponding significance level. This study offers investors and company management a deeper understanding of the elements that contribute to firm value in the manufacturing industry.